Amelioration of Non-Alcoholic Steatohepatitis by Atractylodes macrocephala Polysaccharide, Chlorogenic Acid, and Geniposide Combination Is Associated With Reducing Endotoxin Gut Leakage - Leng, Jing; Tian, Hua-jie; Fang, Yi; Hu, Yi-yang; Peng, Jing-hua (Frontiers in Cellular and Infection Microbiology, 2022)
Gut-derived lipopolysaccharide (LPS) leaking through the dysfunctional intestinal barrier contributes to the onset of non-alcoholic steatohepatitis (NASH) by triggering inflammation in the liver. In the present study, a combination consisting of Atractylodes macrocephala polysaccharide (A), chlorogenic acid (C), and geniposide (G) (together, ACG), was shown to ameliorate NASH in mice and reduce hepatic LPS signaling and endotoxemia without decreasing the abundance of identified Gram-negative bacteria through restoring the intestinal tight junctions. Our data indicated that inhibition of LPS gut leakage by the ACG combination contributed to its amelioration of NASH.